KOMPUTERISASI AKUNTANSI PEMBELIAN KERTAS SECARA KREDIT BERBASIS WEB PADA CV CIPTA GRAFIKA - Yeny Rostiani; Lila Setiyani (Universitas Methodist Indonesia, 2020)
CV Cipta Grafika is a company engaged in printing, for the raw material needs for printing this company buys in cash or credit. In this study, the researcher will discuss the process of purchasing printing materials on credit, because in this process the existing applications have not provided maximum results, namely, there are often errors in the presentation of data or information. The researcher will create a web-based credit purchase and debt recording system with MySQL as the database. The output of this system is the payment of obligations to the supplier which will be due and the supplier's debt recording report can be monitored. It is hoped that this purchasing and recording system will make the payment process easier, avoid mistakes, and can streamline time.